Underwater drone-based eDNA metabarcoding reveals regional differences in fish communities and early detection of alien species around the Korean Peninsula - Tae-Sik Yu; Won-Seok Kim; Ihn-Sil Kwak (Scientific Reports)
Abstract Coastal ecosystems surrounding the Korean Peninsula are undergoing rapid environmental changes driven by global climate warming, highlighting the need for efficient methods to monitor marine biodiversity. This study aimed to analyze fish communities across four coastal regions: the East Sea, South Sea, West Sea, and Jeju using environmental DNA (eDNA) metabarcoding. Underwater drones were employed to collect water samples. A total of 63 sampling sites were surveyed, detecting 167 fish species from 72 families, encompassing tropical, subtropical, temperate, boreal, polar, and deep-water taxa. The East Sea hosted a mix of cold- and warm-water species, while Jeju exhibited a relatively high proportion of tropical and subtropical fish. Additionally, 13 alien species were identified, underscoring the utility of eDNA for the early detection of non-native taxa expanding their ranges in response to ongoing warming trends. This study further validated that eDNA sampling using underwater drones offers a rapid, non-invasive approach to biodiversity assessments, effectively addressing many of the limitations associated with traditional survey techniques. Collectively, these findings highlight the potential of eDNA to generate critical and timely data on fish assemblages the emergence of alien species, providing valuable insights to inform proactive resource management, and climate change research in marine ecosystems.